Cryptococcus neoformans varieties isolated from patients with aids referred to a hospital of São Paulo city during 1996-1999 - Paschoal, Regina C. (2007)
Cryptococcus neoformans is an encapsulated yeast that presents tropism for central nervous system, and causes meningoencephalitis. Cryptococcosis is the most frequent mycosis in patients with AIDS, and it is the cause of high morbidity and mortality. C. neoformans presents two varieties var. neoformans and var. gattii. Cryptococcus neoformans var. neoformans has been world-wide isolated from avian feces, especially pigeon excreta. C. neoformans var. gattii is geographically restricted to tropical and subtropical regions, and it is associated with some trees species, mainly Eucalyptus sp. The proposal of this study was to evaluate the prevalence of Cryptococcus neoformans varieties isolated from 452 cerebrospinal fluid (CSF) samples from 183 patients with AIDS referred to the Instituto de Infectologia Emilio Ribas - Sao Paulo-SP, from 1996 to 1999. CSF samples were cultured on canavanine-glycine-bromothymol blue medium. Of 452 samples, C. neoformans var. neoformans was isolated in 446 (98.7%), and C. neoformans var. gattii. in 6 (1.3%) samples.